Analysis Of Physical Fitness Levels In Madrasah Aliyah Ummul Quro Al-Islami - Arya A, Danu Maulana; Resita, Citra; Suherman, Asep (Jurnal Porkes, 2024)
The purpose of this study was to assess the level of physical fitness in boarding schools. This research is a quantitative approach with survey method. The population in this study were 24 grade XI students who were total sampling. The test instrument was the Indonesian physical fitness test. Data analysis techniques through the stages of reducing, presenting, and making conclusions. Based on the results of the study, the level of physical fitness of students in the 60m running test is in the moderate category of 67%, in the body lift hanging test is in the category of less than 50%, in the lying down test is in the moderate category of 50%, in the upright jumping test is in the category of less than 67%, in the 1200m running test is in the category of less than 67%. Then, the level of physical fitness of female students in the 60m running test is 67% less category, in the body hanging test is 75% less category, in the lying test is 42% moderate category, in the upright jumping test is 33.3% moderate category, in the 1000m running test is 75% less category. Thus, it can be concluded that the level of physical fitness of students in both schools must be improved.